2014
DOI: 10.1371/journal.pone.0115663
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Co-Chaperone CCRP/DNAJC7 in Cyp2b10 Gene Activation and Steatosis Development in Mouse Livers

Abstract: Cytoplasmic constitutive active/androstane receptor (CAR) retention protein (CCRP and also known as DNAJC7) is a co-chaperone previously characterized to retain nuclear receptor CAR in the cytoplasm of HepG2 cells. Here we have produced CCRP knockout (KO) mice and demonstrated that CCRP regulates CAR at multiple steps in activation of the cytochrome (Cyp) 2b10 gene in liver: nuclear accumulation, RNA polymerase II recruitment and epigenetic modifications. Phenobarbital treatment greatly increased nuclear CAR a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 44 publications
(49 reference statements)
2
18
0
Order By: Relevance
“…Although HSP90 appeared to be able to interact with a surface that forms a dimer interface, HSP90 was not critically involved in CAR homodimerization (our unpublished observation). Studies with CCRP KO mice found that while CCRP regulates PB-induced nuclear accumulation of CAR, CCRP also regulates CAR-mediated transcription in the nucleus (11). Active ERK1/2 binds to the XRS peptide near the C terminus of the CAR LBD to keep CAR phosphorylated (7).…”
Section: Discussionmentioning
confidence: 99%
“…Although HSP90 appeared to be able to interact with a surface that forms a dimer interface, HSP90 was not critically involved in CAR homodimerization (our unpublished observation). Studies with CCRP KO mice found that while CCRP regulates PB-induced nuclear accumulation of CAR, CCRP also regulates CAR-mediated transcription in the nucleus (11). Active ERK1/2 binds to the XRS peptide near the C terminus of the CAR LBD to keep CAR phosphorylated (7).…”
Section: Discussionmentioning
confidence: 99%
“…Phenobarbital, is a classically described indirect CAR activator, and it works by modulating the threonine-38 phosphorylation site downstream of its direct interaction with the epidermal growth factor receptor (EGFR) [125]. Cytoplasmic CAR retention protein (CCRP) is speculated to have an alternate role as a co-activator of CAR in the nucleus, and CCRP −/− mice develop steatosis which implies that CAR activity may prevent steatosis [126]. …”
Section: Constitutive Androstane Receptormentioning
confidence: 99%
“…4). Apparently, nuclear translocation is essential but not sufficient for CAR to activate transcription and CAR activation requires distinct processes in the nucleus (Ohno et al, 2014). Recent studies with cytoplasmic CAR retention protein (CCRP) knockout (KO) mice showed that CCRP does not regulate basal intracellular localization of CAR (Ohno et al, 2014).…”
Section: Negishimentioning
confidence: 99%
“…Although CCRP (the cochaperone DNAJC7) was first characterized for accumulating ectopic CAR in the cytoplasm of HepG2 cells , CCRP is now known to regulate CAR in the nucleus (Ohno et al, 2014). CAR-mediated transcription is diverse but tightly regulated in the nucleus.…”
Section: Negishimentioning
confidence: 99%